Waste-based biopolymer slurry for 3D printing targeting construction elements. (December 2022) - Rech, Arianna; Chiujdea, Ruxandra; Colmo, Claudia; Rossi, Gabriella; Nicholas, Paul; Tamke, Martin; Thomsen, Mette Ramsgaard; Daugaard, Anders E.
Abstract: The construction industry consumes significant quantities of mineral-based materials, thereby causing pollution and raw material depletion. To meet projected demands for new buildings, while simultaneously reducing the use of non-renewable materials and fossil-based carbon, there is therefore a strong drive to develop alternative, renewable materials to replace those currently used in this sector. In the present study, we investigate the formulation of waste-based biopolymer slurries for 3D printing as a path towards more sustainable construction elements. The printing formulation was based on xanthan gum as a binder with lignocellulosic waste fibres and particles for reinforcement. At the same time, flow properties were controlled using a combination of bio-based plasticiser (glycerol) and water. First, the amounts of water, plasticiser and waste fillers were optimised to minimise shrinkage and deformation while obtaining the best possible mechanical properties after drying. Different reinforcing fillers were investigated, and it was proven that a minor addition of inorganic material (vermiculite) could significantly improve the material's mechanical properties during printing and in its final form after drying. Furthermore, it was shown how using calcium ions could enhance the binding effect of the xanthan gum and how combining it with an increase in binder concentration could improve the early-age strength of the printed material. The optimised formulations were proven suitable for 3D printing. The addition of vermiculite improved weathering resistance and stability during printing (shrinkage and height), which was illustrated in a bench-scale printing test. Graphical Abstract: ga1 Highlights: Water-based slurries help to combine waste and bio-based materials for 3D printing at the architectural scale. Plasticiser, water, binder, and fillers were optimized to balance flowability and final mechanical properties. Calcium ions as ionic cross-linker enhances the performance of the binder and improves the 3D printing performance. Vermiculite doubles the mechanical properties improves weathering resistance and 3D printing performance.